Annual plant reviews, Volume 42: Oceanography and Marine Biology - Gibson, R. (CRC Press, 2009)
Ever-increasing interest in oceanography and marine biology and its relevance to global environmental issues creates a demand for authoritative reviews summarizing the results of recent research. Oceanography and Marine Biology: An Annual Review has answered this demand since its founding by the late Harold Barnes more than forty years ago. Its objective is an annual consideration of basic areas of marine research, dealing with subjects of special or immediate importance, adding new subjects as they arise.